End-users' Perception of Cybercrimes towards E-banking Adoption and Retention - Taha Abbas; Kashif Arif (JISR on Computing, 2023)
The advancement of information and communication technology (ICT) has resulted in dynamic changes in the operations of various business sectors all over the world, while causing inconvenience to users and making stakeholders' lives easier. However, the advancement in the same has brought major concerns for businesses, such as cybercrime. This study focuses on identifying the impact of cybercrime on the adoption of e-banking services in Pakistan. The study aims to understand the impact of hacking, identity theft and phishing on the adoption of E-banking in Pakistan. The data was collected from 384 banking customers through structured questions containing the demographic questions as well as questions related to the constructs used in the study. The findings of the study suggest that hacking, phishing and identity theft negatively affect the adoption of E-banking in Pakistan. The results of the study are discussed in line with the existing literature. The study limitations and future research areas are also discussed.